Compositional analysis of various local food waste - Mohamed Azizan, Nurul Amirah (2020)
Food is defined as "the wholesome of edible material that intended for human consumption". For the household, the process is included during or after preparation of the food. There are many studies conducted on waste in landfill that process have their own potential to be utilized as a source of energy and available to convert to valued product into the resources. The objective of the study is to analyze and identifies the nutritional value in the composition of local food waste in terms of moisture, ash, protein, fat, and carbohydrates. Besides that, this study is also intended to identify the suitable future product by using proximate analysis. There are 6 types of sample that has been chosen and the result indicated that three important compositions contained in the sample, tea waste high in protein 3.109 ± 0.02 and carbohydrates 79.27 ± 0.96 while coconut 44.42 ± 2.24 respectively.